"Datherini Poem By Abdul Kareem Abu Alshih ,the poet "Stylistic Study - Hassan, Khaled Abdel Aziz (Journal of Humanities & Social Sciences, 2019)
This study has dealt with Abdul Kareem Abu al - Shih Poetry: stylistic study which connects the linguistic structure with its expressive value or significance in order to analyze his poetry in the light of method solidarity because the comprehensive study of the collection –divan must be useful even without method.The study viewed Dtherini poem as various level texts so they were analyzed and their basic elements were counted. Besides, the different structures were contrasted and each linguistic element has its own function in the frame of the text or context. Moreover, all of the linguistic elements were connected to the poet who invented them to create his creative poetry.The study consists of three chapters: (Stylistic rhythmical phenomena, Stylistic structural phenomena and Stylistic semantic phenomena).At rhythmical level: Abu al - Shih has carefully selected his rhymes and internal acoustic formulations and their harmony with the theme of the poem.At structural level: Abu al - Shih intensively used the composition structures (Command) as semantic indications specially the use of the verb as a significant element in building up distinguished texts.At semantic level: the semantic fields such as (love) dominated the linguistic elements in his poems as appeared in quotation specially the religious quotations.The study viewed Abu al - Shih as a poet who was able to highly employ the elements of the linguistic system with its various levels to serve his poetic purposes in the expressive, emotive, impressionistic, and aesthetic aspects, so he has combined varied techniques in the same text.This study did not follow the conventional approach in processing the classical poetic texts, but it followed a modern critical approach which tends to the objective approach as much as possible.
Keywords: stylistics; Jordanian poetry; Abdul Karim Abu Al-Sheeh; stylistic analysis; stylistic levels